A Systematic Review of the Causes and Management of Ischaemic Stroke Caused by Nontissue Emboli. (16th October 2017) - Judge, Ciaran; Mello, Sarah; Bradley, David; Harbison, Joseph
Abstract : Introduction . The inadvertent or purposeful introduction of foreign bodies or substances can lead to cerebral infarction if they embolize to the brain. Individual reports of these events are uncommon but may increase with the increased occurrences of their risk factors, for example, intra-arterial procedures. Method . We searched EMBASE and MEDLINE for articles on embolic stroke of nontissue origin. 1889 articles were identified and screened and 216 articles were ultimately reviewed in full text and included in qualitative analysis. Articles deemed relevant were assessed by a second reviewer to confirm compatibility with the inclusion criteria. References of included articles were reviewed for relevant publications. We categorized the pathology of the emboli into the following groups: air embolism (141 reports), other arterial gas embolisms (49 reports), missiles and foreign bodies (16 reports), and others, including drug embolism, cotton wool, and vascular sclerosant agents. Conclusion . Air and gaseous embolism are becoming more common with increased use of interventional medical procedures and increased popularity of sports such as diving. There is increasing evidence for the use of hyperbaric oxygen for such events. Causes of solid emboli are diverse. More commonly reported causes include bullets, missiles, and substances used in medical procedures.